ANALISIS PENGARUH PROFITABILITAS, PERTUMBUHAN PERUSAHAAN, UKURAN PERUSAHAAN DAN LIKUIDITAS TERHADAP STRUKTUR MODALPADA PERUSAHAAN PERBANKAN - DIAH FEBRIANTI, ELITA (Jurnal Ilmu Manajemen (JIM), 2015)
Abstract :This study aims to analyze the influence of profitability, growth, firm size and liquidity to the capital structure of the banking company is listed on the Indonesian Stock Exchange in 2009-2013. The independent variables in this study consisted of profitability, growth, firm size and liquidity. Samples taken in this study consisted of 18 commercial banks listed on the Indonesian Stock Exchange. The results showed that all the variables simultaneously significant to the capital structure. Partially growth and liquidity significant on corporate capital structure.While the profitability does not significant with the capital structure. Increased profitability may decrease due to the higher debt because profitability of the companies tend to use internal funds in the form of retained earnings to fund its operations. In addition, firm size does not significant with the capital structure because the possibility of the company already has a internal allocation of funds to finance its operations. Keyword : capital structure, profitability, growth, size and liquidity.